Kebijakan Pidana Terhadap Masyarakat Hukum Adat Pasca Putusan Mahkamah Konstitusi Republik Indonesia : Mahkamah Konstitusi, Putusan, Masyarakat Hukum Adat - Nilam Kurnia; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2023)
This study is based on the Constitutional Court Decision No. 95/PUU-XII/2014 which states that it accepts the conditional constitutionality of Article 50(3)(e) and (i) of Forestry Law No. 41 of 1999. when the article is declared constitutional to the extent that it is understood by all people, and it is prohibited to cut trees or harvest or collect forest products in the forest without the right or permission from the authorized agency, except for people who have lived in the forest for generations and not for commercial purposes and livestock grazing in officially designated forest areas, except for people who have lived in the forest for generations and not for commercial purposes. Although the Constitutional Court only accepted the wording of the paragraph, rejected the wording of several other paragraphs of the law and deemed the paragraph of Law No. 18 of 2013 on the Prevention and Elimination of Deforestation unacceptable, the Constitutional Court affirmed the existence of customary law communities inhabiting forest areas. The Federal Constitutional Court held that people who have a very strong relationship with the forest should be exempted from criminal provisions.